Phytochemical analysis and toxicity test of some selected herbal preparation in market - Julia, Abdullah (Universiti Sains Malaysia, 2008)
The phytochemical and the cytotoxicity studies of some selected locally available herbal preparation on VERO cell lines were done. Three products have been purchased from the local market namely TAOl, EN02 and AM03. Each product contained mixture of herbs. For TA01 product, it was claimed to Eurycoma longifolia. Second product, that is EN02, it was claimed to contain Sauropus androgynus (cekak manis) and for AM03, it was claim to contain rhizome of Curcuma zedoaria, and the Elephantopus scaber (tapak liman). Successive extraction of the herbal products TAO 1, EN02 and AM03 yields ( 1.66%, 1.06% and 3.2% in petroleum ether), (10.6%, 32% and 14.0% in methanol) and (9.26%, 4.65% and 9.63% in water) respectively. Phytochemical test was done for all the extracts. Every product was tested positive for the presence of alkaloid, saponin, coumarin, flavonoids, tannin and phenolic compound except for anthraquinones. Cytotoxicity test was done for methanol and water for all of the extract. From the cytotoxicity test, all the herbal preparation has not shown toxic effect on VERO cells. All extracts showed no ICso at concentration of 1.59 x 10-3 J.1g/ml to O.lJ.Lg/ml.